Optimalisasi Keuangan Perusahaan Melalui Sistem Manajemen Keuangan - Sherlyna Masaylina; Dewi Sartika; Hatifa Nadila; Suria (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
Having a strong grasp on financial management is essential for the success of any organization. This paper thoroughly Examines financial management as a complex system of interconnected processes that necessitate collaboration among Investors, creditors, and managers. The report explores the role of financial management within an organization and its Impact on achieving economic optimization. Based on thorough research, this review paper highlights the key components Of effective financial management: planning, budgeting, forecasting, and monitoring. The text highlights the significance of Effective communication and collaboration among all stakeholders in financial decision-making. Through careful Monitoring of financial performance, financial management ensures that an organization optimizes its available resources.